Physiotherapy treatment experiences of persons with persistent musculoskeletal pain: A qualitative study. (2nd January 2021) - Calner, Tommy; Isaksson, Gunilla; Michaelson, Peter
ABSTRACT: The aim of this study was to explore and describe the physiotherapy treatment experiences of persons with persistent musculoskeletal pain. Eleven participants with persistent musculoskeletal pain in the back, neck, or shoulders were included in the study. Data was collected via semi-structured interviews and were analysed with qualitative content analysis. The analysis resulted in the theme "Towards acceptance and management of pain", comprising four sub-themes: 1) Establishing and maintaining a therapeutic alliance; 2) Being active, taking initiative and facing challenges; 3) Appreciating guidance, incentive and having a sounding board; and 4) Acquired knowledge and new body awareness change behaviours. The theme and sub-themes describe how the participants used increased knowledge, awareness, movements and exercises learned from the physiotherapy treatment to develop strategies for managing pain and the process of acceptance. A trusting relationship and continual dialogue with the physiotherapist was considered to be important. The participants were actively involved in the process as exercises, activities and other treatment modalities were individualized. This was rewarding but also challenging and required effort on their part. The physiotherapist's initiatives and actions were an important incentive and means of support.